Antifungal Prevention of Systemic Candidiasis in Immunocompetent ICU Adults: Systematic Review and Meta-Analysis of Clinical Trials. Issue 11 (November 2017) - Dupont, Hervé; Mahjoub, Yazine; Chouaki, Taieb; Lorne, Emmanuel; Zogheib, Elie
Abstract : Objectives: The aim of this study was to identify the impact of antifungal prevention in critically ill immunocompetent adult patients on mortality and subsequent infection. Data Sources: A systematic review and meta-analysis of randomized controlled trials comparing any antifungal use versus placebo to prevent candidiasis in ICU patients were performed. Study Selection: Searches were performed on PubMed, Embase, Scopus, main conference proceedings, andClinicalTrials.gov, as well as reference lists. Data Extraction: The primary outcomes were mortality and invasive candidiasis. The secondary outcome was the rate of Candida albicans and nonalbicans strains after treatment. A random effect model was used, and sensitivity analysis was performed for both outcomes. Results are expressed as risk ratios and their 95% CIs. Data Synthesis: Nineteen trials (10 with fluconazole, four with ketoconazole, one with itraconazole, three with micafungin, and one with caspofungin) including 2, 792 patients were identified. No individual trial showed a decreased mortality rate. Combined analysis showed that preventive antifungal did not decrease mortality (risk ratio, 0.88; 95% CI, 0.74–1.04; p = 0.14) but significantly decreased secondary fungal infections by 50% (risk ratio, 0.49; 95% CI, 0.35–0.68; p = 0.0001). No shift across nonalbicans strains was observed during treatment (risk ratio, 0.62; 95% CI, 0.19–1.97; p = 0.42). However, publication biases preclude any definite conclusions for prevention of infection. Conclusions: Antifungal prevention of systemic candidiasis in immunocompetent critically ill adults did not reduce mortality and may have decreased secondary fungal infection rates. However, significant publication bias was present. Abstract : Supplemental Digital Content is available in the text.